Pelatihan Pembuatan Media Ajar Berbasis Animasi kepada Kelompok Guru TK - Isnaini Muhandhis; Alven S. Ritonga; M. Harist Murdani; Ishaq A.M. (Prosiding, 2022)
The teaching and learning process in several kindergartens in the Gayungan area of Surabaya during this pandemic, students were given assignments from the books and assignment sheets were distributed every Monday. During the pandemic, because most children study independently at home, it would be better if the teaching materials provided varied. Making innovative teaching materials can increase children's interest in learning. One alternative teaching media is animation. This service program aims to carry out training in making animation teaching materials using Ms Power Point and help make some teaching materials for kindergartens. The training is carried out with a participatory approach, where each teacher is guided to practice the material being taught directly. The results of this service program are: (1) increasing teacher competence in making animated teaching materials, (2) creating interesting animated teaching materials